2005
DOI: 10.1180/0026461056950278
|View full text |Cite
|
Sign up to set email alerts
|

Fe isotope fractionation during the precipitation of ferrihydrite and transformation of ferrihydrite to goethite

Abstract: Ferrihydrite and goethite are amongst the most important substrates for the sorption of contaminants in soil and other environmental media. Isotopic studies of the transition elements, particularly those that exhibit more than one oxidation state and show pH- and/or redox-sensitive behaviour at low temperatures, have been shown to be potentially useful present-day and past proxies for redox (or palaeoredox) conditions. We have made preliminary investigations of Fe isotope fractionation that take place during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Oxidative precipitation of ferrihydrite is a combination of (2) and (3) because of the instability of Fe(III) aq species in seawater, producing an overall enrichment in the heavy isotope (Bullen et al, 2001). Further transformation of ferrihydrite to goethite has also been observed to cause isotope fractionation over a time scale of 70 h, but the age of the samples analysed in this study are much younger (Clayton et al, 2005). Adsorption and desorption of Fe(II) onto Fe-oxyhydroxide or Fe-sulfide phases is another potential fractionation mechanism in the plume, with isotopically heavy Fe(II) adsorbing to mineral surfaces.…”
Section: Isotope Fractionation In the Buoyant Plume And The Isotope Cmentioning
confidence: 81%
“…Oxidative precipitation of ferrihydrite is a combination of (2) and (3) because of the instability of Fe(III) aq species in seawater, producing an overall enrichment in the heavy isotope (Bullen et al, 2001). Further transformation of ferrihydrite to goethite has also been observed to cause isotope fractionation over a time scale of 70 h, but the age of the samples analysed in this study are much younger (Clayton et al, 2005). Adsorption and desorption of Fe(II) onto Fe-oxyhydroxide or Fe-sulfide phases is another potential fractionation mechanism in the plume, with isotopically heavy Fe(II) adsorbing to mineral surfaces.…”
Section: Isotope Fractionation In the Buoyant Plume And The Isotope Cmentioning
confidence: 81%
“…A previous experiment has shown that Fe isotopic fractionation during the transformation of ferrihydrite into goethite increased with decreasing the ferrihydrite to goethite ratios, ultimately leading to an enrichment of the lighter Fe isotopes in goethite (Clayton et al, 2005). As we noted above, Fe (oxyhydr)oxides are the most possible products of the alteration of the dark minerals in the marine sediment rather than the crystallized Fe oxides (Yokoyama and Nakashima, 2005).…”
Section: Source Origin and Reactivation Of Fe (Oxyhydr)oxidementioning
confidence: 85%
“…In recent years, researchers have also explored the natural variations of Ti (Zhu et al 2002b), Sn (Clayton et al 2005), Ag (Woodland et al 2005), and Te (Fehr et al 2004) isotopes, and although the variations are generally smaller than 0.1‰ amu −1 , these metal isotopes may find future applications in paleoceanography. Larger variations of stable isotope compositions of metalloids such as Se and Ge have been also reported.…”
Section: Other Elementsmentioning
confidence: 99%